The Moderating Role of Self Silencing in Relationship Between Attachment and Marital Satisfaction in Married People - Parisa Moghadas sharif; zahra Abdekhodaie; Leili Panaghi (روانشناسی بالینی و شخصیت)
Introduction:The present study aims to investigate the moderating role of self-silencing in the relationship between attachment and marital satisfaction among married individuals.Method: This study employed a correlational regression design. The statistical population consisted of married Iranian individuals aged 18 to 60 years, from which a sample of 300 participants (150 women and 150 men) was selected using convenience sampling. Participants completed the Enrich Marital Satisfaction, Self-Silencing, and Close Relationship Experience questionnaires. The data were analyzed using the Pearson correlation coefficient and hierarchical regression in SPSS.Results: The relationship between avoidant and anxious attachment styles and all dimensions of self-silencing, except for the self-sacrifice dimension, is negative and significant in relation to marital satisfaction. The relationship is insignificant only in the self-sacrifice dimension. It was also concluded from the regression analysis that all attachment styles and self-silencing can predict marital satisfaction. The results of the moderated regression analysis indicated that the moderating effects of the Silencing the Self and Divided Self dimensions on the relationship between anxious attachment and marital satisfaction, as well as the moderating effects of the Self-Sacrifice and Self-Silencing dimensions on the relationship between avoidant attachment and marital satisfaction, are significant.Discussion and Conclusion: The results of this study indicate that varying levels of certain dimensions of self-silencing influence the relationship between attachment styles and marital satisfaction. Furthermore, managing attachment styles and self-silencing can enhance marital satisfaction.